Cyborgs, Sexuality, and the Undead : The Body in Mexican and Brazilian Speculative Fiction - Ginway, M. Elizabeth (Book collections on Project MUSE., 2020)
"Expands the purview of speculative fiction in all its incarnations (science fiction, fantasy, horror) beyond the traditional Anglo-American context to focus on work produced in Mexico and Brazil, providing a historical overview from 1870 to the present, and addressing the technological, cultural, and social consequences of modernity and its implications for the human body"--